Exploring factors affecting Chinese adolescents’ perceived usefulness and engagement with a stress management app: a qualitative study - Zhou, Xiaoyun; Bambling, Matthew; Bai, Xuejun; Smith, Anthony C.; Edirippulige, Sisira (Frontiers in Psychology, 2023)
Providing adolescents with stress management interventions via mobile apps has potential for overcoming barriers to traditional in-person services, such as stigma, cost and travel. However, the effectiveness remains uncertain and engagement level remains low.Therefore, it is essential to understand adolescents' user experience of such apps, however, such research is scarce. This study aimed to address this research gap by exploring factors affecting Chinese adolescents' perceived usefulness and engagement of a stress management app, which was developed for them.Methods: A qualitative study design involving focus group interviews and inductive thematic analysis was adopted. A purposive sampling method was employed, resulting in five focus groups (n=39 adolescents).Results: Two themes emerged: (1) mechanism and determinants of usefulness and (2) facilitators and barriers to engagement. The app was found to be helpful in managing chronic and simple stressors by promoting positive behavior, cognition, and physical changes. Relevance to real-life situations, peer support, and planning and monitoring features were found to increase usefulness.Participants suggested adding one-on-one chat support for managing acute stressors. Multimedia, logical content arrangement, combining psychoeducation and skills training, gamification, customization, and an appealing user interface were engaging factors for adolescents, whilst text-删除了: behaviour heavy content, pedagogical and monotonous tones, technical issues were found to disengage adolescents.Stress management apps should involve simple and evidence-based coping skills training, target adolescents' real-life problems, promote positive peer influence, address both chronic and acute stressors. Additionally, such apps should have logical arrangement of content, be interactive and customizable, and involve multimedia and gamification features to engage adolescents.